HAK ASASI MANUSIA (HAM) DALAM RELASI SUAMI ISTRI: KAJIAN KITAB ‘UQūD AL-LUJAIN KARYA SYAIKH NAWAWI AL-BANTANI - Ulum, Bahrul; Amatul Jadidah (LP3M IAI Al-Qolam, 2023)
The background to this research is that the book 'Uqūd al-Lujain by Syaikh Nawawi al-Bantani has invited debate and is considered irrelevant in the millennial era. This research explores the aspects of human rights in the book. It is qualitative research uses normative legal approach or library research with contect analysis which aims to understand human rights in ‘Uqūd al-Lujain profoundly. The results reveal that the description of the relationship between a husband and wife in ‘Uqūd al-Lujain by Sheikh Nawawi al-Bantani is a relationship that firmly emphasizes the importance of knowing the rights and obligations between husband and wife in the view of religious texts, includes several stories and quotes some opinions of the scholars. Among the most important standards of general freedom are correspondence or equality and non-segregation or non-discrimination. Regarding couples, 'Uqūd al-Lujain has received many claims because it is considered to provide an inaccurate understanding of human rights standards, especially towards women. However, basically Sheikh Nawawi's focus is to understand the etiquette of husband and wife according to his reading of religious texts based on the Qur’an and hadith. This is because his inclination towards aspects of Sufism is very strong. Thoughts that can be categorized as traditional and Sufistic have colored the writing of this book, and of course this was in accordance with the spirit of the times (zeitgeist) of that time.